DIGESTIBILITY, CARCASS QUALITY AND ECONOMIC BENEFIT OF RABBITS FED VARIOUS AGRO-INDUSTRIAL BYPRODUCTS AS FIBRE SOURCES - Samson, K.; Yusuf, S. Z.; Abdullahi, A. I.; Aminu, S. I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This experiment was carried out to evaluate the response of growing rabbits to various diets containing different agro-industrial byproducts. Twenty-four (24) mongrel weaner rabbits of mixed sexes, aged between 6 to 8 weeks were used for the experiment. The rabbits were randomly allocated to four (4) experimental treatments of six (6) rabbits per treatment, replicated three (3) times in a completely randomized design with two (2) rabbits per replicate. Four experimental diets were formulated and designated as T1, T2, T3, and T4. T1 (control diet) contained 20% Maize Offal (MO), while T2, T3 and T4 contained 20% each of brewers dried grain (BDG), sorghum offal (SO) and millet offal (MLO) respectively as their main fibre sources. Data collected were subjected to one-way Analysis of Variance. Digestibility study showed all parameters were significantly influenced (P<0.05) except for dry matter. The nutrients were properly digested due to the high values of nutrient digestibility recorded. Carcass characteristics showed significant differences (P<0.05) in respect of live weight, slaughter weight, dressing weight, eviscerated weight, dressing percentage, hind limbs, thorax and loins among the dietary treatments except for forelimbs, neck and abdominal fats which were not significant (P>0.05). Parameters measured on internal organs weight showed no significant difference (P>0.05) among the treatment groups. Rabbits fed sorghum offal based diet recorded the highest cost savings of N208.38. It was concluded that rabbits performed best on sorghum offal-based diet. Hence, it was recommended that 20% sorghum offal-based diet can be included in the diet of weaner rabbits without negative effects on digestibility, carcass yield and economics of production as it reduces the high cost associated with the use of conventional feed ingredients in rabbits’ production.